The Rejection of Rohingya Refugees in Aceh: A Scientific Analysis from Human Rights and Public Policy Perspectives - Athoillah, Syafiq; Hendra (Al Mabhats : Jurnal Penelitian Sosial Agama, 2024)
This scientific analysis critically examines the polemic surrounding the rejection of Rohingya refugees in Aceh, Indonesia. Drawing from the fields of human rights and public policy, the study explores the reasons behind the rejection, including concerns about the behaviour and attitudes of Rohingya people in refugee camps. The analysis provides a comprehensive examination of the issue, considering the ethical implications and socioeconomic considerations from a scientific standpoint. This study aims to Aceh's policy on refugees and asylum seekers, focusing on the legal framework and the country's approach as a transit nation. The analysis includes an exploration of Indonesia's handling of refugees, provisions for interception and rescue, and the absence of long-term resettlement options. The article also discusses the implications of Indonesia's stance on the Rohingya crisis and the sustainability of Aceh's hospitality towards refugees. The article raises questions about the future prospects for greater hospitality and the granting of rights to refugees in Indonesia and neighbouring countries. The research results also show Approaching the rejection of Rohingya refugees in Aceh through a scientific lens allows policymakers to navigate this issue effectively. By integrating human rights principles, ethical considerations, and socioeconomic factors, policies can be formulated to protect refugees' rights while promoting the well-being of the host community